Determination of Maturity Parameters of Indian Mango Cultivars Based on Eating Quality during Natural Ripening - N. Jha, Shyam; Jaiswal, Pranita; Narsaiah, Kairam; Kumar, Ramesh; Sharma, Rajiv; Kaur, Poonampreet; Bhardwaj, Rishi (Journal of Agricultural Engineering, 2013)
Variation in physico-chemical characteristics as total soluble solids (TSS), titratable acidity (TA), dry matter (DM) and eating quality viz. appearance (APR) and taste (TST) scores of nine major Indian mango cultivars were studied as a function of harvesting stage. TSS, TA and DM varied between 7.6 to 22.1Â°Brix, 6.31 to 0.24% and 14.84 to 31.67%, respectively. The surface of first and second harvest mangoes got shriveled and did not ripen well except cv. Chausa and Langra obtained from Uttar Pradesh, Maldah from Bihar, and Mallika from Orissa. However, mangoes from third harvest ripened well and had higher sensory scores except cv. Alphonso obtained from Karnataka and Neelum from Tamil Nadu. Among selected cultivars, mango showing superior eating quality exhibited variations in TSS, TA and DM in the range of 11.7 to 14.6 Â°Brix, 0.51 to 6.28% and 18.94 to 27.36%, respectively, at the time of harvesting. The correlation coefficient for TSS, TA and DM with appearance and taste scores ranged between 0.98 to 0.68, 0.99 to 0.78 and 0.91 to 0.35, respectively. The measured quality parameters may be taken as maturity indicators to decide the harvest date of mango cultivars, or could further be used to develop the maturity index.